Does type of feeding affect body composition in very low birth weight infants? – A prospective cohort study - Nina Mól; Magdalena Zasada; Przemko Kwinta (Pediatrics and Neonatology)
Background: The aim of the study was to analyse body composition of preterm infants fed with either breast milk or formula compared to a control group of full-term newborns. Methods: Fifty-three newborns were enrolled: a group of 34 very low birth weight (VLBW) preterm newborns subdivided into a formula-fed (n = 23; group A) and breast milk-fed (n = 11; group B) group, and a control group of 19 full-term infants (group C). Their body composition was assessed by a bioelectrical impedance analysis (BIA) either at the estimated time of birth in the VLBW group or during the 1st week of life in the full-term group. Results: There was no difference in body weight or length between any of the three studied groups. However, we discovered that fat free mass (% FFM) was lower (83.5% vs. 85.5%; p < 0.01), while fat mass (% FM) was higher (16.4% vs.14.5%; p < 0.01) in group A compared to full-term newborns. There were no such differences in FFM (84.3% vs. 85.5%; p = 0.13) or FM (15.7% vs. 14.5%; p = 0.13) between group B and control. Conclusion: To sum up, the VLBW infants fed with breast milk shared similar body composition with the full-term infants, while the formula-fed VLBW developed higher amounts of adipose tissue and lower amounts of fat-free mass. This is the first study to expose differences in fat tissue content attributed to type of provided nutrition, which has become significant as early as estimated time of birth despite the comparable weight. Key Words: body composition, breastfeeding, formula feeding, preterm infants